2013
DOI: 10.1016/j.jml.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking familiarity: Remember/Know judgments in free recall

Abstract: Although frequently used with recognition, a few studies have used the Remember/Know procedure with free recall. In each case, participants gave Know judgments to a significant number of recalled items (items that were presumably not remembered on the basis of familiarity). What do these Know judgments mean? We investigated this issue using a source memory/free-recall procedure. For each word that was recalled, participants were asked to (a) make a confidence rating on a 5-point scale, (b) make a Remember/Know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 41 publications
6
66
0
Order By: Relevance
“…Such a prospect relies on the assumption that these tests are all, in their own way, measures of some "core" episodic memory ability. The selfreport judgments described here, as well as the remember/know judgments in previous studies (e.g., Tulving 1985;Holland and Smulders 2011;Easton et al 2012;Mickes et al 2013) provide hope that this may, indeed, be the case, although further research is needed.…”
Section: Discussionmentioning
confidence: 52%
“…Such a prospect relies on the assumption that these tests are all, in their own way, measures of some "core" episodic memory ability. The selfreport judgments described here, as well as the remember/know judgments in previous studies (e.g., Tulving 1985;Holland and Smulders 2011;Easton et al 2012;Mickes et al 2013) provide hope that this may, indeed, be the case, although further research is needed.…”
Section: Discussionmentioning
confidence: 52%
“…Target recollection is presumably being experienced because these items were just read out of consciousness, but nevertheless, context recollection is unsuccess ful for a sizeable percentage. Mickes et al (2013) reported such findings for young adults. Their subjects recalled word lists and then made source judgments about recalled items, with source memory being inaccurate for 37% of recalled items.…”
Section: Context Recollection and Target Recollectionmentioning
confidence: 71%
“…Gomes (2014) reported further data on target-recollectionwithout-context-recollection in recall that mapped failures of con text recollection with independent measures of target recollection. Although, intuitively, recall involves target recollection, it has been proposed that some portion of it actually relies on nonrecol lective processes such as reconstruction (Brainerd, Reyna, & Howe, 2009) or familiarity (Mickes et al, 2013). To allow for that possibility, Gomes used the dual-retrieval model of recall to obtain independent estimates of recollective and nonrecollective retrieval for individual targets.…”
Section: Context Recollection and Target Recollectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Jacoby, Toth and Yonelinas (1993) have stressed that recollection is a strategic process by which retrieval of specifics can bring to bear on the recognition decision. On the other hand, others, such as Mickes, Seale-Carlisle and Wixted (2013) stress that it is the production of material associated to a retrieval cue that characterises information as recollected. One such clear category of contextual information is source memory: the ability to retrieve features of memories that give rise to their episodic character (Mitchell & Johnson, Consistent with prevailing conceptions of recollection, neuropsychological studies report deficits both in source memory tasks and in paradigms emphasizing the strategic control requirement of recollection.…”
Section: Introductionmentioning
confidence: 99%